Effect of Thrombin on Phosphorylation of Platelet Membrane Proteins - Steiner, M (Thrombosis and Haemostasis, 1976)
The effect of thrombin on the phosphorylating activity of platelet membranes was compared to that of trypsin. Preincubation of non-32P phosphorylated platelet membranes with or without either of these two enzymes resulted in a considerable loss of membrane protein kinase activity which was most severe when trypsin was used. Protein kinase activity and endogenous protein acceptors decreased in parallel. 32P-phosphorylated membranes showed a slow but progressive loss of label which was accelerated by trypsin. Thrombin under these conditions prevented the loss of 32P-phosphate. These results are interpreted to indicate a thrombin-induced destruction of a phosphoprotein phosphatase. The protein kinase activity of phosphorylated platelet membranes using endogenous or exogenous protein substrates showed a significant reduction compared to non-phosphorylated membranes suggesting a deactivation of protein kinase by phosphorylation of platelet membranes. Neither thrombin nor trypsin caused a qualitative change in the membrane polypeptides accepting 32P-phosphate but resulted in quantitative alterations of their ability to become phosphorylated.